2014
DOI: 10.3892/br.2014.343
|View full text |Cite
|
Sign up to set email alerts
|

Predictive prognostic role of miR-181a with discrepancy in the liver and serum of genotype 4 hepatitis C virus patients

Abstract: Abstract. microRNA (miRNA) expression in organs does not always represent their quantity in serum. A disparity in the expression of miR-181a has been reported in the tissues and serum of hepatocellular carcinoma (HCC) patients. Since hepatitis C virus (HCV) is a major cause of HCC and miR-181a has never been studied in HCV, the present study aimed to investigate the miR-181a expression profile in genotype 4 (GT4)-HCV patients to evaluate whether this pattern is also apparent in HCV. RNA was extracted from live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Moreover, the expression of miR-181a in HCC liver tissues was also up-regulated compared with the normal cells [3436]. However, Elhelw et al reported that no difference in miR-181a expression was observed in liver tissues and peripheral blood mononuclear cell (PBMCs) of patients compared with controls [37]. Korhan et al reported miR-181a-5p is down-regulated in hepatocellular carcinoma and suppresses motility, invasion and branching-morphogenesis by directly targeting c-Met [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of miR-181a in HCC liver tissues was also up-regulated compared with the normal cells [3436]. However, Elhelw et al reported that no difference in miR-181a expression was observed in liver tissues and peripheral blood mononuclear cell (PBMCs) of patients compared with controls [37]. Korhan et al reported miR-181a-5p is down-regulated in hepatocellular carcinoma and suppresses motility, invasion and branching-morphogenesis by directly targeting c-Met [38].…”
Section: Discussionmentioning
confidence: 99%
“… 57 Serum levels of miR-181a were significantly elevated in SVR patients following treatment compared to NR patients and treatment-naïve SVRs. 58 IFN-λ3 expression is strongly associated with favorable response to IFN-α and RBV in HCV infected patients. However, HCV infection induces the expression of miR-208b and miR-499a-5p, which in turn downregulates IFN-λ3 expression.…”
Section: Cellular Mirnas In Response To Ifn Therapy and Hcv Infectionmentioning
confidence: 95%
“… 50 miR-181a expression was significantly upregulated in the serum of HCV patients compared to the healthy controls. 58 The serum miR-181a expression level in HCV patients is inversely correlated with the level of viremia, as well as liver enzymes (ALT, AST). Levels of miR-125b and miR-146a were also increased in the serum of CHC patients compared to healthy controls.…”
Section: Circulatory Mirnas As Biomarkers In Hcv Infectionmentioning
confidence: 99%
“…By contrast, another study by Elhelw et al [90] has demonstrated upregulation of miR-181a in serum samples of HCV genotype 4-infected individuals and downregulation in HCV-infected Huh7 cells. In addition, the inverse correlation between miR-181a serum levels, viral load, and liver enzymes was observed.…”
Section: Mirnas and Hcv Infectionmentioning
confidence: 80%